Cave millipedes of the United States. XVI. Two new species from Oregon Caves National Monument, Oregon (Chordeumatida, Conotylidae and Caseyidae) - Shear, William A.; Crawford, Rodney L. (Zootaxa, 2019)
Two new species of millipedes are described from Oregon Caves National Monument, Josephine County, Oregon, USA: Taiyutyla caseophila, n. sp. (Conotylidae), a troglophile; and Opiona catorycha, n. sp. (Caseyidae), a troglobiont found in at least one other cave in the region. We also provide a brief discussion of the invertebrate biodiversity of Oregon Cave.